Interfacial Bond Properties between Normal Strength Concrete and Epoxy Resin Concrete - Nannan Sun; Yifan Song; Wei Hou; Hanhao Zhang; Datong Wu; Yuan Li; Yuan Gong (Advances in Materials Science and Engineering)
It is necessary to pay attention to the bonding strength of the interface between precast normal strength concrete (NSC) and cast-in-place epoxy resin concrete (EMR) when using EMR as a repair or filling material or an overlay in bridges’ rehabilitation. However, the performances of epoxy concrete are different due to differential mix ratios; thus, the bonding properties between various epoxy resin concrete and cement concrete are not completely the same. This article investigated the interfacial bond properties between NSC and ERC by direct tensile, push-out, and slant shear test with specimens of special size and structure and observed the interfacial bond strength and corresponding failure modes. The minimum bond strength under direct tension was 0.72 MPa, while the minimum bond strength was 1.71 MPa and 3.19 MPa for the push-out test and slant shear test, respectively. Results indicated that the slant shear test specimens with an inclination angle of 45° are not suitable for the slant shear test due to higher compressive stress. Furthermore, the cohesion and friction coefficient of interface bond strength were calculated inversely in accordance with the results obtained from the corresponding direct tensile and slant shear tests. The minimum cohesion value was 1.71 MPa, and the minimum friction coefficient value was 0.46.